The Influence Quality of Work Life on Employee Performance in Class IIa Special Criminal institution in Gunung Sindur - Rahayu, Widya Puji; Kusmiyanti, Kusmiyanti (prodima@fe.uika-bogor.ac.id, 2023)
The main aspect that needs to be considered by the management of every organization in carrying out an activity is Quality of Work Life (QWL) which it can be called quality of work life in Indonesian. This study aims to determine whether the quality of work life affects the performance of the Class IIA Gunung Sindur Special Prison employees. The methodology used is quantitative with a descriptive approach. The population is all employees of the Class IIA Gunung Sindur Special Prison. Samples were taken using a random sampling technique of 80 people obtained from the Slovin formula. After testing using the F test, it can be concluded that the quality of work life has a very significant effect on employee performance. Descriptive analysis that has been carried out by researchers shows that the performance of employees gets a very good predicate.